The Deep Section: Karst Urbanism in Town Branch Commons - Kate Orff; Geni Wirth; Anne Weber (Oz, 2015)
Nothing is without context. Every lawn, parking lot, skyscraper, or national park has been shaped by a myriad of factors natural and humanmade. As a research-driven practice, our work at SCAPE is empowered by the complex layers of systems that act upon a site: rates of urban development, economic shifts, ecological flows of plants and animals, hydrological systems, and circulation systems, to name just a few.